Photoelectrochemical photoanode based on sensitization of environment-friendly manganese-doped copper-indium-gallium-sulfur quantum dots and preparation method and photoelectrochemical application of photoelectrochemical photoanode

By using manganese-doped copper indium gallium sulfur quantum doped on titanium dioxide thin film photoelectrode and performing ZnS passivation treatment, the shortcomings of existing heavy metal quantum dot photoelectrochemical photoanodes in photogenerated exciton transfer/separation efficiency and chemical stability are solved, and an efficient and stable photoelectrochemical system is achieved.

CN119530864APending Publication Date: 2025-02-28UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411654607.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing heavy metal-based quantum dot photoelectrochemical photoanodes have shortcomings in photoexciton transfer/separation efficiency and chemical stability, limiting their efficient and stable solar energy conversion applications.

Method used

Manganese-doped copper indium gallium sulfur quantum dots are used to synthesize high-quality quantum dots by spin coating and co-thermal method, and deposition is carried out on titanium dioxide thin film photoelectrode. Combined with ZnS passivation treatment, the photoexciton separation/transfer efficiency and photoelectric/chemical stability are improved.

Benefits of technology

It significantly improves the photoexciton separation/transfer efficiency and exciton lifetime of manganese-doped copper indium gallium sulfur quantum doped, improves the saturated photocurrent and stability of the photoelectrochemical system, and provides a new method for green, environmentally friendly and efficient solar energy conversion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention provides a photoelectrochemical photoanode based on sensitization of environment-friendly manganese-doped copper-indium-gallium-sulfur quantum dots and a preparation method and photoelectrochemical application of the photoelectrochemical photoanode. The photoelectrochemical photoanode is a quantum dot sensitized titanium dioxide film photoelectrode, and the preparation method of the photoelectrochemical photoanode comprises the following steps: (1) preparing a transparent titanium dioxide barrier layer on conductive glass through a spin coating method, coating a titanium dioxide mesoporous layer through a blade coating method after the transparent titanium dioxide barrier layer is dried, and performing high-temperature calcination to obtain a mesoporous titanium dioxide film photoelectrode; (2) synthesizing a high-quality copper-indium-gallium-sulfur quantum dot by adopting a co-heating method, and doping a manganese element in a high-temperature nucleation stage to obtain a manganese-doped copper-indium-gallium-sulfur quantum dot with high charge separation / transfer efficiency; and (3) soaking the mesoporous titanium dioxide film photoelectrode in a quantum dot / toluene solution, depositing a quantum dot solution by using an electrophoretic deposition method, drying the quantum dot solution, and carrying out ZnS passivation treatment on the surface of the quantum dot solution to obtain the quantum dot sensitized titanium dioxide film photoelectrochemical cell photoanode. According to the invention, an electrode is packaged, and the quantum dot sensitized titanium dioxide film photoelectrode is used as an anode and is assembled with a Pt counter electrode and an Ag / AgCl reference electrode to form the quantum dot photoelectrochemical cell. According to the invention, the environment-friendly quantum dot photoelectrochemical cell without heavy metal components is realized, the photo-generated charge separation / transfer transportation efficiency of the quantum dots is improved through element doping, and high-performance environment-friendly quantum dot photoelectrochemical solar conversion application is further realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cell electrode materials, and specifically relates to an environmentally friendly manganese-doped copper indium gallium sulfide quantum dot-sensitized titanium dioxide thin film photoanode, and a preparation method and photoelectrochemical application thereof. Background Art

[0002] Photoelectrochemical technology can directly utilize solar energy to convert clean hydrogen energy, and is one of the important ways to solve the energy crisis and environmental pollution problems in the future. So far, low-cost, large-scale preparation, solution-based synthesis of semiconductor colloidal quantum dots has shown great potential in solar energy conversion applications due to its unique high light absorption coefficient and size / component adjustable optical properties. The high-performance quantum dot photoelectrochemical applications currently developed are mainly concentrated on quantum dots containing toxic II-VI and IV-VI heavy metals Cd and Pb. Therefore, it is of practical significance to develop environmentally friendly quantum dot materials that do not contain heavy metal elements to adapt to the future development of environmentally friendly green chemistry. In addition, pure quantum dots often have problems such as poor optical properties and chemical stability due to the large number of defects on their surfaces to form complex centers and high sensitivity to the external environment, which further limits the efficiency breakthrough of quantum dot photoelectrochemical applications. Therefore, it is of great significance to rationally design and prepare efficient and stable photoelectrochemical systems of environmentally friendly quantum dots that do not contain heavy metals.

[0003] At present, the photoelectrochemical photoanodes based on environmentally friendly quantum dots show low saturation photocurrent and photo / chemical stability due to the slow transfer / separation of photogenerated excitons in the reaction. Therefore, the development of environmentally friendly I-III-VI group quantum dots with high photogenerated exciton separation / transfer efficiency and high efficiency and stability is the key to the research and development of green and environmentally friendly and efficient solar energy conversion applications in the future. Summary of the invention

[0004] In view of the above-mentioned prior art, the present invention provides a manganese-doped copper indium gallium sulfide quantum dot-sensitized titanium dioxide thin film photoanode, and its preparation method and photoelectrochemical application, and utilizes element doping to rationally regulate the separation / transfer efficiency of photogenerated excitons in its quantum dots to promote the development of green, environmentally friendly, efficient and stable quantum dot photoelectrochemistry.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] An environmentally friendly manganese-doped copper indium gallium sulfide quantum dot-sensitized titanium dioxide thin film photoanode, and a preparation method and photoelectrochemical application thereof, comprising the following steps:

[0007] S1. Prepare a transparent titanium dioxide barrier layer on the conductive glass by spin coating, and after drying, apply a titanium dioxide mesoporous layer by blade coating, and prepare a mesoporous titanium dioxide thin film photoelectrode after high temperature calcination;

[0008] Further, the specific operation of step S1 is: using FTO conductive glass as a substrate, using a 100 μL pipette to absorb 60 to 100 μL of Ti-Nanoxide BL / SC solution and spin-coating it on the surface of the substrate, and forming a transparent titanium dioxide barrier layer after drying, and using a quantitative scraping method to coat the titanium dioxide mesoporous layer, and calcining at 500° C. in a muffle furnace for 30 to 50 minutes at a heating rate of 5° C. / min, and obtaining a mesoporous titanium dioxide thin film photoelectrode after natural cooling;

[0009] Furthermore, the spin coating acceleration and the spin coating speed are 3000 rpm and 5000 rpm, respectively, the thickness of the formed transparent titanium dioxide barrier layer is 5-7 μm, the drying temperature is 80°C, the thickness of the scraped mesoporous titanium dioxide layer is 7-9 μm, the high temperature calcination temperature is 500°C, and the time is 30-50 min;

[0010] S2. Synthesize high-quality copper indium gallium sulfide quantum dots by co-thermal method, and dope manganese element in the high-temperature nucleation stage to obtain manganese-doped copper indium gallium sulfide quantum dots with high charge separation / transfer efficiency;

[0011] Furthermore, the specific operation of step S2 is: manganese-doped copper indium gallium sulfur quantum dots are prepared by the following steps: first, a copper source, an indium source, a gallium source, and a solvent are sequentially added into a 50 mL three-necked flask, degassed at room temperature after mixing, and then heated to 210° C. to 230° C. under nitrogen protection, and after the reaction temperature stabilizes, a sulfur source and an elemental manganese precursor are added dropwise, and then kept warm for 5 to 15 minutes, and quenched in a water bath to obtain the result.

[0012] Furthermore, the copper source, indium source, gallium source and solvent used in the synthesis of the quantum dots are copper iodide, indium acetate, gallium acetylacetonate and octadecene, respectively, and their amounts are 0.125mmol, 0.25mmol, 0.25mmol and 5mL, respectively. The sulfur source is dodecanethiol, and the amount is 4-6mL. The elemental manganese precursor is 0.1mmol manganese chloride, and the solvent is 1mL dodecanethiol, and the amount is 0.1mL-0.5mL.

[0013] S3, immersing the mesoporous titanium dioxide thin film photoelectrode in a quantum dot / toluene solution, and using an electrophoretic deposition method to deposit the quantum dot solution, and after drying, performing a ZnS passivation treatment on the surface to obtain a quantum dot-sensitized titanium dioxide thin film photoelectrochemical cell photoanode;

[0014] Furthermore, the specific operation of step S3 is: taking a quantitative 1-2 mL of the synthesized manganese-doped copper indium gallium sulfur quantum dot stock solution, adding 1 mL of toluene solution, shaking and coarse centrifuging, the centrifugal rate is 3000 rpm, the centrifugal time is 1 minute, taking the upper clear liquid and adding ethanol solution to 10 mL and then centrifuging twice, the centrifugal rate is 12000 rpm, the centrifugal time is 3-5 minutes, and then the quantum dots after centrifugation are redispersed in the toluene solution.

[0015] Furthermore, the mesoporous titanium dioxide thin film photoelectrode is placed in a redispersed quantum dot / toluene solution, and the quantum dots are electrophoretically deposited in the mesoporous titanium dioxide thin film photoelectrode at a DC bias voltage of 100 to 200 V for 2 to 3 hours to obtain a quantum dot-sensitized titanium dioxide thin film photoelectrode.

[0016] S4. The quantum dot-sensitized titanium dioxide thin film photoelectrode is used as the anode, and is assembled with a Pt counter electrode and an Ag / AgCl reference electrode into a quantum dot photoelectrochemical cell.

[0017] Further, the titanium dioxide thin film photoelectrode surface passivation treatment in step S4 is specifically performed as follows: the photoelectrode is immersed in a zinc acetate solution for 1 min, washed with a methanol solution and then dried with a nitrogen gun, then immersed in a nine-water and sodium sulfide solution for 1 min, washed with a methanol / water solution and then dried with a nitrogen gun, the above operation is repeated 6 to 10 times, and finally dried with a nitrogen gun, after which a ZnS protective layer of different thicknesses is formed on the surface, and the electrode surface is encapsulated with epoxy resin to retain about 0.1 cm 2 working area.

[0018] Furthermore, the present invention also provides a photoelectrochemical cell based on an environmentally friendly manganese-doped copper indium gallium sulfide quantum dot-sensitized titanium dioxide thin film photoanode, which uses a manganese-doped copper indium gallium sulfide quantum dot-sensitized photoelectrode as an anode, a Pt electrode as a counter electrode, an Ag / AgCl electrode as a reference electrode, an electrolyte of a sodium sulfide / sodium sulfite mixed aqueous solution (pH of about 12.5), and a light source of a standard solar irradiation xenon lamp (AM1.5G) with an intensity of 100 mW / cm 2 .

[0019] The environmentally friendly manganese-doped copper indium gallium sulfide quantum dot-sensitized titanium dioxide thin film photoanode, its preparation method and photoelectrochemical application provided by the present invention have the following beneficial effects:

[0020] 1. The present invention synthesizes environmentally friendly copper indium gallium sulfide colloidal quantum dots. By doping the copper indium gallium sulfide colloidal quantum dots with manganese elements, the photogenerated carrier separation / transfer efficiency and exciton lifetime are improved while maintaining the efficient light absorption / emission of the quantum dots themselves.

[0021] 2. The present invention obtains a quantum dot-sensitized titanium dioxide photoelectrochemical photoanode through the synthesized manganese-doped copper indium gallium sulfide colloidal quantum dots, overcomes the photocorrosion of the photoanode surface through surface passivation, and effectively improves the photoelectric / chemical stability of the photoanode in the photoelectrochemical reaction.

[0022] 3. Based on the above-mentioned environmentally friendly manganese-doped copper indium gallium sulfide quantum dot photoelectrochemical system under 1 standard solar irradiation (AM1.5G, 100mW / cm 2 ) has a high efficiency saturation photocurrent (~10.5mA / cm 2 ) and excellent photoelectrochemical stability, providing a new method for promoting future low-cost, green and environmentally friendly, high-performance quantum dot photoelectrochemical hydrogen production systems, and promoting practical industrial applications such as photovoltaic hydrogen production in the future new energy field. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope image of the morphology of Mn-doped CuInGaS quantum dots;

[0024] Figure 2 is the X-ray diffraction pattern of Mn-doped CuInGaS quantum dots;

[0025] Figure 3 is the ultraviolet absorption curve of Mn-doped CuInGaS quantum dots;

[0026] Figure 4 The steady-state fluorescence spectrum and transient fluorescence lifetime diagram of Mn-doped CuInGaS quantum dots;

[0027] Figure 5 This is a test diagram of the photoelectrochemical performance and stability of Mn-doped CuInGaS quantum dots sensitization. DETAILED DESCRIPTION

[0028] Example 1

[0029] Research on environmentally friendly manganese-doped copper indium gallium sulfide quantum dot-sensitized photoelectrodes, their preparation process and photoelectrochemical applications, as follows:

[0030] (1) Using FTO conductive glass as the substrate, 60 μL of Ti-Nanoxide BL / SC solution was taken with a 100 μL pipette and spin-coated on the substrate surface. After drying, a transparent titanium dioxide barrier layer with a thickness of 5 μm was formed. After drying at 80°C, a titanium dioxide mesoporous layer with a thickness of 7 μm was further scraped on the surface. Subsequently, the solution was calcined at 500°C in a muffle furnace for 30 min and naturally cooled to obtain a mesoporous titanium dioxide thin film photoelectrode.

[0031] (2) Environmentally friendly manganese-doped copper indium gallium sulfur colloidal quantum dots were synthesized by a co-thermal method, mainly consisting of the following steps: 0.125mmol CuI, 0.25mmol In(Ac)3, 0.25mmol Ga(acac)3, and 5mL octadecene were added to a 50mL three-necked flask in sequence, mixed evenly, and degassed at room temperature. Finally, the mixture was heated to 210°C under nitrogen protection, and 4mL dodecanethiol and 0.1mL elemental manganese precursor solution (0.1mmol MnCl2 dispersed in 1mL dodecanethiol solution) were added dropwise, followed by keeping at 210°C for 5min and quenching in a water bath.

[0032] (3) Take a certain amount of 1 mL of the synthesized manganese-doped copper indium gallium sulfide quantum dot stock solution, add 1 mL of toluene solution, shake well, and then roughly centrifuge at a centrifugal rate of 3000 rpm for 1 minute. After the rough centrifugation, take the upper clear liquid and add ethanol solution to 10 mL, then perform a second centrifugation at a centrifugal rate of 12000 rpm for 3 minutes. Then, the quantum dots after centrifugation are redispersed in 9 mL of toluene solution.

[0033] (4) The prepared mesoporous titanium dioxide thin film photoelectrode was placed in a redispersed quantum dot / toluene solution, and the quantum dots were electrophoretically deposited in the mesoporous titanium dioxide thin film photoelectrode at a DC bias voltage of 100 V for 2 hours to obtain a quantum dot-sensitized titanium dioxide thin film photoelectrode.

[0034] (5) A ZnS passivation protective layer is grown on the surface of the prepared quantum dot-sensitized titanium dioxide thin film photoelectrode. The specific steps are as follows: the photoelectrode is immersed in a 0.1 M zinc acetate / methanol solution for 1 min, washed with the methanol solution and dried with a nitrogen gun, then immersed in a 0.1 M nonahydrate and sodium sulfide / equal volume methanol and water mixed solution for 1 min, washed with the methanol / water solution and dried with a nitrogen gun, the above operation is repeated 6 times, and finally dried with a nitrogen gun, and then the electrode is encapsulated with epoxy resin to retain about 0.1 cm 2 working area.

[0035] Example 2

[0036] Research on environmentally friendly manganese-doped copper indium gallium sulfide quantum dot-sensitized photoelectrodes, their preparation process and photoelectrochemical applications, as follows:

[0037] (1) Using FTO conductive glass as the substrate, 80 μL of Ti-Nanoxide BL / SC solution was taken with a 100 μL pipette and spin-coated on the substrate surface. After drying, a transparent titanium dioxide barrier layer with a thickness of 6 μm was formed. After drying at 80°C, a titanium dioxide mesoporous layer with a thickness of 8 μm was further scraped on the surface. Subsequently, the solution was calcined at 500°C in a muffle furnace for 40 min and naturally cooled to obtain a mesoporous titanium dioxide thin film photoelectrode.

[0038] (2) Environmentally friendly manganese-doped copper indium gallium sulfide colloidal quantum dots were synthesized by a co-thermal method, mainly consisting of the following steps: 0.125mmol CuI, 0.25mmol In(Ac)3, 0.25mmol Ga(acac)3, and 5mL octadecene were added to a 50mL three-necked flask in sequence, mixed evenly, and degassed at room temperature. Finally, the temperature was raised to 220°C under nitrogen protection, and 5mL dodecanethiol and 0.3mL elemental manganese precursor solution (0.1mmol MnCl2 dispersed in 1mL dodecanethiol solution) were added dropwise, followed by keeping at 220°C for 10min and quenching in a water bath.

[0039] (3) Take a quantitative 1.5 mL of the synthesized manganese-doped copper indium gallium sulfide quantum dot stock solution, add 1 mL of toluene solution, shake well, and then roughly centrifuge at a centrifugal rate of 3000 rpm for 1 minute. After the rough centrifugation, take the upper clear liquid and add ethanol solution to 10 mL, then perform a second centrifugation at a centrifugal rate of 12000 rpm for 4 minutes. Then, the quantum dots after centrifugation are redispersed in 9 mL of toluene solution.

[0040] (4) The prepared mesoporous titanium dioxide thin film photoelectrode was placed in a redispersed quantum dot / toluene solution, and the quantum dots were electrophoretically deposited in the mesoporous titanium dioxide thin film photoelectrode at a DC bias voltage of 150 V for 2.5 hours to obtain a quantum dot-sensitized titanium dioxide thin film photoelectrode.

[0041] (5) A ZnS passivation protective layer is grown on the surface of the prepared quantum dot-sensitized titanium dioxide thin film photoelectrode. The specific steps are as follows: the photoelectrode is immersed in a 0.1 M zinc acetate / methanol solution for 1 min, washed with the methanol solution and dried with a nitrogen gun, then immersed in a 0.1 M nonahydrate and sodium sulfide / equal volume methanol and water mixed solution for 1 min, washed with the methanol / water solution and dried with a nitrogen gun, the above operation is repeated 8 times, and finally dried with a nitrogen gun, and then the electrode is encapsulated with epoxy resin to retain about 0.1 cm 2 working area.

[0042] Example 3

[0043] Research on environmentally friendly manganese-doped copper indium gallium sulfide quantum dot-sensitized photoelectrodes, their preparation process and photoelectrochemical applications, as follows:

[0044] (1) Using FTO conductive glass as the substrate, 100 μL of Ti-Nanoxide BL / SC solution was taken with a 100 μL pipette and spin-coated on the substrate surface. After drying, a transparent titanium dioxide barrier layer with a thickness of 7 μm was formed. After drying at 80°C, a titanium dioxide mesoporous layer with a thickness of 9 μm was further scraped on the surface. Subsequently, the solution was calcined at 500°C in a muffle furnace for 50 min and naturally cooled to obtain a mesoporous titanium dioxide thin film photoelectrode.

[0045] (2) Environmentally friendly manganese-doped copper indium gallium sulfide colloidal quantum dots were synthesized by a co-thermal method and were mainly prepared by the following steps: 0.125mmol CuI, 0.25mmol In(Ac)3, 0.25mmol Ga(acac)3, and 5mL octadecene were added to a 50mL three-necked flask in sequence, mixed evenly, and degassed at room temperature. Finally, the temperature was raised to 230°C under nitrogen protection, and 6mL dodecanethiol and 0.5mL elemental manganese precursor solution (0.1mmol MnCl2 dispersed in 1mL dodecanethiol solution) were added dropwise, followed by keeping at 230°C for 10min and quenching in a water bath.

[0046] (3) Take a certain amount of 2 mL of the synthesized manganese-doped copper indium gallium sulfide quantum dot stock solution, add 1 mL of toluene solution, shake well, and then roughly centrifuge at a centrifugal rate of 3000 rpm for 1 minute. After the rough centrifugation, take the upper clear liquid and add ethanol solution to 10 mL, then perform a second centrifugation at a centrifugal rate of 12000 rpm for 5 minutes. Then, the quantum dots after centrifugation are redispersed in 9 mL of toluene solution.

[0047] (4) The prepared mesoporous titanium dioxide thin film photoelectrode was placed in a redispersed quantum dot / toluene solution, and the quantum dots were electrophoretically deposited in the mesoporous titanium dioxide thin film photoelectrode at a DC bias voltage of 200 V for 3 hours to obtain a quantum dot-sensitized titanium dioxide thin film photoelectrode.

[0048] (5) A ZnS passivation protective layer is grown on the surface of the prepared quantum dot-sensitized titanium dioxide thin film photoelectrode. The specific steps are as follows: the photoelectrode is immersed in a 0.1 M zinc acetate / methanol solution for 1 min, washed with the methanol solution and dried with a nitrogen gun, then immersed in a 0.1 M nonahydrate and sodium sulfide / equal volume methanol and water mixed solution for 1 min, washed with the methanol / water solution and dried with a nitrogen gun, the above operation is repeated 10 times, and finally dried with a nitrogen gun, and then the electrode is encapsulated with epoxy resin to retain about 0.1 cm 2 working area.

[0049] The phase and morphology of the manganese-doped copper indium gallium sulfide quantum dots prepared in Example 1 were analyzed, and the X-ray diffraction pattern and transmission electron microscopy analysis showed that Figure 1 and Figure 2 The UV-visible absorption spectrum, steady-state fluorescence photoluminescence spectrum and transient fluorescence photoluminescence lifetime of manganese-doped copper indium gallium sulfide quantum dots in toluene were analyzed. Figure 3 , Figure 4 It can be seen that the manganese-doped copper indium gallium sulfide quantum dots of the present invention improve the exciton fluorescence lifetime while maintaining the efficient light absorption / emission of the quantum dots themselves.

[0050] A photoelectrochemical cell was constructed based on the photoanode obtained in Example 1. The specific parameters were as follows: a manganese-doped copper indium gallium sulfur quantum dot-sensitized titanium dioxide thin film photoanode was used as the anode, a Pt electrode was used as the counter electrode, a reference electrode was an Ag / AgCl electrode, an electrolyte was a sodium sulfide / sodium sulfite mixed aqueous solution (pH was about 12.5), and a light source was a standard solar irradiation xenon lamp (AM1.5G) with an intensity of 100 mW / cm 2 The performance of the photoelectrochemical system was tested, and the photocurrent saturation density can reach 10.5mA / cm 2 , and 3h has a stability of 59.2%. It can be seen that the photoelectrochemical system sensitized by manganese-doped copper indium gallium sulfide quantum dots of the present invention has excellent photoelectrochemical activity and stability.

[0051] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A method for preparing an environmentally friendly titanium dioxide thin film photoelectrochemical cell photoanode based on manganese-doped copper indium gallium sulfide quantum dots sensitization, characterized in that: The following steps are involved: S1. Prepare a transparent titanium dioxide barrier layer on the conductive glass by spin coating, and after drying, apply a titanium dioxide mesoporous layer by blade coating, and prepare a mesoporous titanium dioxide thin film photoelectrode after high temperature calcination; S2. Synthesize high-quality copper indium gallium sulfide quantum dots by co-thermal method, and dope manganese element in the high-temperature nucleation stage to obtain manganese-doped copper indium gallium sulfide quantum dots with high charge separation / transfer efficiency; S3, immersing the mesoporous titanium dioxide thin film photoelectrode in a quantum dot / toluene solution, and using an electrophoretic deposition method to deposit the quantum dot solution, and after drying, performing a ZnS passivation treatment on the surface to obtain a quantum dot-sensitized titanium dioxide thin film photoelectrochemical cell photoanode; S4. The quantum dot-sensitized titanium dioxide thin film photoelectrode is used as the anode, and is assembled with a Pt counter electrode and an Ag / AgCl reference electrode into a quantum dot photoelectrochemical cell.

2. The preparation method according to claim 1, characterized in that: The specific process of step S1 is: using FTO conductive glass as a substrate, a transparent titanium dioxide barrier layer is prepared on the conductive glass by spin coating, after it is dried, a titanium dioxide mesoporous layer is coated by blade coating, and a mesoporous titanium dioxide thin film photoelectrode is obtained after high-temperature calcination.

3. The preparation method according to claim 1, characterized in that: The thickness of the formed transparent titanium dioxide barrier layer is 5-7 μm, the drying temperature is 80°C, the thickness of the scraped mesoporous titanium dioxide layer is 7-9 μm, the high-temperature calcination temperature is 500°C, and the time is 30-50 minutes.

4. The preparation method according to claim 1, characterized in that: The specific process of step S2 is: the co-thermal method for synthesizing quantum dots mainly includes the following steps: first, the copper source, indium source, gallium source, and solvent are added to a 50mL three-necked flask in sequence, mixed and degassed at room temperature, then heated to 210°C to 230°C under nitrogen protection, and after the reaction temperature stabilizes, the sulfur source and elemental manganese precursor are added dropwise, then kept warm for 5-15 minutes, and quenched in a water bath to obtain.

5. The preparation method according to claim 1, characterized in that: The copper source, indium source, gallium source and solvent used in the synthesis of the quantum dots are copper iodide, indium acetate, gallium acetylacetonate and octadecene, respectively, and their dosages are 0.125mmol, 0.25mmol, 0.25mmol and 5mL, respectively. The sulfur source is dodecanethiol, and the dosage is 4-6mL. The elemental manganese precursor is 0.1mmol manganese chloride, and the solvent is 1mL dodecanethiol.

6. The preparation method according to claim 1, characterized in that: The specific process of step S3 is: immersing the mesoporous titanium dioxide thin film photoelectrode in the toluene solution in which the quantum dots are re-dispersed after purification, and electrophoretically depositing the quantum dots in the mesoporous titanium dioxide thin film photoelectrode at a DC bias voltage of 100 to 200 V for 2 to 3 hours to obtain a quantum dot-sensitized titanium dioxide thin film photoelectrode.

7. The preparation method according to claims 1 to 6, characterized in that: A ZnS protective layer was grown on the surface of the prepared quantum dot-sensitized titanium dioxide thin film photoelectrode using continuous ion layer deposition. The specific steps were as follows: the photoelectrode was immersed in a zinc acetate solution for 1 min, washed with a methanol solution and then dried with a nitrogen gun, then immersed in a nonaqueous solution and a sodium sulfide solution for 1 min, washed with a methanol / water solution and then dried with a nitrogen gun, the above operation was repeated 3 to 10 times, and finally dried with a nitrogen gun, and then the electrode was encapsulated with epoxy resin.

8. The preparation method according to claim 7, characterized in that: The dosage of the zinc acetate solution is 0.1M, and the solvent is 20mL of methanol solution; the dosage of the nonahydrate and sodium sulfide solution is 0.1M, and the solvent is 20mL of a mixed solution of equal volumes of methanol and water. The reserved area after epoxy resin encapsulation is ~0.1cm 2 . 9 . An environmentally friendly manganese-doped copper indium gallium sulfide quantum dot-sensitized titanium dioxide thin film photoelectrochemical anode prepared by the preparation method according to any one of claims 1 to 8 .

10. A photoelectrochemical cell based on an environmentally friendly manganese-doped copper indium gallium sulfide quantum dot-sensitized titanium dioxide thin film photoelectrochemical photoanode, characterized in that: The photoelectrode based on the above-mentioned environmentally friendly manganese-doped copper indium gallium sulfide quantum dots sensitization is the working electrode, the Pt electrode is the counter electrode, the Ag / AgCl is the reference electrode, the electrolyte is a sodium sulfide / sodium sulfite mixed aqueous solution, and the light source is 1 standard solar irradiation (AM1.5G) with an intensity of 100mW / cm 2 .